2016
DOI: 10.1038/srep29072
|View full text |Cite
|
Sign up to set email alerts
|

Expansion of amphibian intronless interferons revises the paradigm for interferon evolution and functional diversity

Abstract: Interferons (IFNs) are key cytokines identified in vertebrates and evolutionary dominance of intronless IFN genes in amniotes is a signature event in IFN evolution. For the first time, we show that the emergence and expansion of intronless IFN genes is evident in amphibians, shown by 24–37 intronless IFN genes in each frog species. Amphibian IFNs represent a molecular complex more complicated than those in other vertebrate species, which revises the established model of IFN evolution to facilitate re-inspectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
192
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(199 citation statements)
references
References 53 publications
7
192
0
Order By: Relevance
“…A diverse array of type I IFN genes should constitute a beneficial trait, likely through functional specialization of the multiple copies or ability to escape virus inhibition (see below, Part 2). This view is also supported by the recent discovery of expanded intronless type I (and type III) IFN in frogs, besides type I and type III IFN genes with introns as found in fish [13,32]. Thus far, no intronless type I IFN genes have been found in fish, and all type I IFN genes identified in the coelacanth genome have introns [33].…”
Section: Fish Type I Interferons: An Astonishing Diversitymentioning
confidence: 86%
“…A diverse array of type I IFN genes should constitute a beneficial trait, likely through functional specialization of the multiple copies or ability to escape virus inhibition (see below, Part 2). This view is also supported by the recent discovery of expanded intronless type I (and type III) IFN in frogs, besides type I and type III IFN genes with introns as found in fish [13,32]. Thus far, no intronless type I IFN genes have been found in fish, and all type I IFN genes identified in the coelacanth genome have introns [33].…”
Section: Fish Type I Interferons: An Astonishing Diversitymentioning
confidence: 86%
“…considered that the scenario might be the case at least in X. tropicalis, and probably in the amphibian lineage, as intronless and intron-containing type I IFNs have been identified in a similar amphibian model species, X. laevis (Sang et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…While this manuscript was in preparation and review, intronless type I IFNs were identified from another amphibian model species X. laevis by Blecha and coworkers, and inductive expression and antimicrobial roles of intronless type I IFNs in X. laevis against influenza viruses and a pathogenic bacterium Listeria monocytogenes were also examined (Sang et al, 2016). The discovery of intronless type I IFNs both in X. laevis and X. tropicalis implies that intronless and intron-containing type I IFN genes may coexist commonly in the Xenopus, and probably in the amphibian lineage.…”
Section: Discussionmentioning
confidence: 99%
“…Interferons (IFNs) 3 represent a group of cytokines that are able to induce resistance to virus infections in treated cells. Most vertebrates possess three types (or families) of IFNs, based on similarities in gene and protein sequences and structures, receptor utilization, and biological functions, which are shared among the members of each IFN type but are distinct between the three IFN types.…”
Section: Interferon Kingdommentioning
confidence: 99%